Odpowiedzi

2009-12-20T00:28:13+01:00
2009-12-20T00:55:08+01:00
A) A = (2;5), B = (-2;1) , C = 2;4)
wektor AB = [-2-2,1-5] = [-4,-4]
wektor BC = [2 +2,4-1] = [4,3]
wektor AC = [2-2, 4-5] = [0,-1]
c = AB, a =BC, b = AC
c² = (-4)² +(-4)² = 16 + 16 = 32
a² = 4² + 3² = 16 + 9 = 25
b² = 0² + (-1)² = 1
25 + 1 ≠ 32
Ten trójkąt nie jest prostokątny,ale rozwartokątny.
b)
A = (-4;2), B = (3;5), C = (-4 ; -5)
wektor AB =[3 +4, 5-2] = [7,3]
wektor BC =[-4-3,-5-5] = [-7,-10]
wektor AC = [ -4 +4, -5 -2] = [0,-7]
c = AB, a = BC, b = AC
c² = 7² + 3² = 49 + 9 = 58
a² = 49 + 100 = 149
b² = 49
58 + 49 ≠ 149
Ten trójkąt nie jest prostokątny, ale rozwartokątny.
c)
A = ( 2;-2), B =(-3; -4), C = (0 ; 0)
wektor AB = [-3-2,-4 +2] = [-5,-2]
wektor BC = [0+3,0+4] = [3,4]
wektor AC =[0-2,0+2] = [ -2,2]
c = AB, a = BC, b = AC
c² = 25 + 4 = 29
a² = 9 + 16 = 25
b² = 4 + 4 = 8
25 + 8 ≠ 29
Ten trójkąt nie jest prostokątny, ale ostrokątny.
1 1 1